2009
DOI: 10.1021/ma900327d
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Charge Screening and Significant Conductivity Enhancement of Conducting Poly(3,4-ethylenedioxythiophene):Poly(styrenesulfonate)

Abstract: This article reports a novel method to significantly enhance the conductivity of conducting poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) films through a treatment with aqueous solutions of various salts, such as copper(II) chloride. Conductivity enhancement by a factor of about 700 was observed. Many salts were investigated, and the conductivity enhancement depended on the softness parameter of cations and the concentration of the salts in solution. A salt like copper(II) chloride or ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
226
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(232 citation statements)
references
References 40 publications
6
226
0
Order By: Relevance
“…[ 36 ] Even at room temperature, the HNO 3 treatment easily removed the PSS domains from the PEDOT:PSS because the strong screening effect reduced the Coulombic interaction between the positively charged PEDOT and the negatively charged PSS dopants. [ 13,37 ] However, the HNO 3 treatment did not induce any redox reactions on the PEDOT domains as was demonstrated by the Raman spectroscopy and XPS results. Therefore, the conductivity enhancement is solely due to an improvement in both the n and µ , which originated from the wileyonlinelibrary.com PSS removal and led to the formation of highly ordered and densely packed PEDOT:PSS fi lms as depicted in Figure 6 .…”
Section: Resultsmentioning
confidence: 64%
“…[ 36 ] Even at room temperature, the HNO 3 treatment easily removed the PSS domains from the PEDOT:PSS because the strong screening effect reduced the Coulombic interaction between the positively charged PEDOT and the negatively charged PSS dopants. [ 13,37 ] However, the HNO 3 treatment did not induce any redox reactions on the PEDOT domains as was demonstrated by the Raman spectroscopy and XPS results. Therefore, the conductivity enhancement is solely due to an improvement in both the n and µ , which originated from the wileyonlinelibrary.com PSS removal and led to the formation of highly ordered and densely packed PEDOT:PSS fi lms as depicted in Figure 6 .…”
Section: Resultsmentioning
confidence: 64%
“…[ 11,104 ] On one hand, the cation effect was discussed by choosing the salts of CuCl 2 , AgNO 3 , InCl 3 , LiCl, NaCl, MgCl 2 , and NiCl 2 . [ 104 ] The result indicated that Cu 2+ , Ag + , and In 3+ with positive softness parameters could enhance the conductivity of the PEDOT:PSS fi lm by 2 orders in magnitude, while other salts of Li + , Na + , Mg 2+ , and Ni 2+ , the cation of which has the negative softness parameter, gave rise to negligible effect on the conductivity. As known, the softness parameter of an ion is related to the binding energy of this ion to other species, and a cation with a positive (or negative) softness parameter is a soft (or hard) Lewis acid, as presented in Table 3 .…”
Section: Salt Solution Treatmentmentioning
confidence: 99%
“…Besides the organic compounds, the introduction of ionic liquids [33] or anionic surfactant [34] into the PEDOT:PSS aqueous solution can also significantly enhance the conductivity of PEDOT:PSS. Treating the PEDOT:PSS with carboxylic, inorganic acids [35], polar organic compounds [4,36] and salt aqueous solution are other ways [37,38]. In such treating methods, solution of material was dropped onto the layer of PEDOT:PSS or layer rinsed into the solution.…”
Section: Introductionmentioning
confidence: 99%